The Dialectic of Islam Nusantara and Its Contribution To The Development of Religious Moderation In Indonesia - Theguh Saumantri (FOKUS Jurnal Kajian Keislaman dan Kemasyarakatan, 2022)
Islam Nusantara refers to identity and religious character. The archipelago people accept Islam because of the close relationship between Islam and the fundamental cultural values of the Indonesian people. The dialectic of Islam Nusantara can be seen through the characteristics of religion that make it different from the religious patterns in some parts of the world, including showing a moderate attitude. Moderation, a guide for maintaining balance and justice in the nation's unity, can become harmony for religion, culture, and politics. In Islam, moderation is the middle wasatha ummah, namely moderate people who adhere to the principle of the bainiyyah (in between). The research method was library research by making books and library materials about Islam Nusantara a reference and primary source. The research results reported that Islam Nusantara, with its moderation movement, has brought together the universal Islam fundamental values by accumulating local values that make the beauty of religious moderation in Indonesia.